Macierzyństwo jako wartość w historiach sukcesu rosyjskich kobiet-przedsiębiorczyń - Abassy, Małgorzata (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
The paper is devoted to motherhood as a culture-creating and meaning-making value, in an individual existential experience. Revealing the semantic scope of the word “motherhood” by lexical and cultural context analyses was the aim of the research. The group of the Russian women-entrepreneurs was selected as a case study. An assumption was made that values and the relations between them create the net which sustain social structure in its communication aspect. It was concluded that, despite the changing socio-cultural context, the essence of motherhood as not only a biological function but also ontological one – as associated with creation – has not been changed. It is archetypical and autotelic value, and it makes the basis of culture.